2014
DOI: 10.1007/s13197-014-1626-x
|View full text |Cite
|
Sign up to set email alerts
|

Iron (II)-chelating activity of buffalo αS-casein hydrolysed by corolase PP, alcalase and flavourzyme

Abstract: Iron is a vital substance for human health which participates in many biochemical reactions. It also act as initiator for many harmful oxidative process. Buffalo αS-casein enriched fraction (80 %) was hydrolysed independently by corolase PP (H1), alcalase (H2), flavourzyme (H3) and sequentially by alcalase-flavourzyme (H4). After ultrafiltration (10 and 3 kDa) hydrolysates were analysed for their iron chelation activity using ferrozine. For H1 group of hydrolysates highest iron (II)-chelation activity (265.58 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Therefore, we used a combination of Alcalase and Flavorzyme. It has been reported that these 2 enzymes can efficiently hydrolyze milk proteins (Jaiswal et al, 2015;Ghosh et al, 2017). Our results also revealed that these enzymes completely hydrolyzed α-LA and β-LG as well as the GMP contained in G-WPC.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, we used a combination of Alcalase and Flavorzyme. It has been reported that these 2 enzymes can efficiently hydrolyze milk proteins (Jaiswal et al, 2015;Ghosh et al, 2017). Our results also revealed that these enzymes completely hydrolyzed α-LA and β-LG as well as the GMP contained in G-WPC.…”
Section: Discussionsupporting
confidence: 71%
“…There are many studies where not only Alcalase, but other proteases were also used to obtain the hydrolysate with iron-chelating properties. However, in most of them, Alcalase was reported to produce the peptides with the highest iron-chelating ability, as it can be seen in some experiments made with scad (Decapterus maruadsi) processing byproducts [549,571], buffalo αS-casein [572] and marine mackerel processing byproducts…”
Section: Hydrolysis Of Animal Proteinsmentioning
confidence: 99%
“…At present, the conventional methodologies of quantification involve the use of expensive reagents and equipment such as ferrozine or atomic absorption. Such investigations have already been conducted for drinking water (Viollier, Inglett, Hunter, Roychoudhury, & Van Cappellen, 2000), cow and buffalo milk (Jaiswal, Bajaj, Mann, & Lata, 2015), wine (Nguyen & Waterhouse, 2018), buttermilk solids (Wong & Kitts, 2001), yogurt, kefir and cream cheese (Unal, 2012), in addition to brown polymeric macromolecules (melanoidins) (Morales, Fernández-Fraguas, & Jiménez-Pérez, 2005) and contaminated soils (that may be subsequently transferred into food crops) (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%